Copper ion salts of arylthiotetrathiafulvalenes: synthesis, structure diversity and magnetic properties - Ma, Longfei; Sun, Jibin; Lu, Xiaofeng; Zhang, Shangxi; Qi, Hui; Liu, Lei; Shao, Yongliang; Shao, Xiangfeng (Beilstein Journal of Organic Chemistry, 2015)
The combination of CuBr2 and arylthio-substituted tetrathiafulvalene derivatives (1–7) results in a series of charge-transfer (CT) complexes. Crystallographic studies indicate that the anions in the complexes, which are derived from CuBr2, show diverse configurations including linear [Cu(I)Br2]–, tetrahedral [Cu(II)Br4]2–, planar [Cu(II)2Br6]2–, and coexistence of planar [Cu(II)Br4]2– and tetrahedral [Cu(II)Br3]– ions. On the other hand, the TTFs show either radical cation or dication states that depend on their redox potentials. The central TTF framework on most of TTFs is nearly planar despite the charge on them, whereas the two dithiole rings on molecule 4 in complex 4·CuBr4 are significantly twisted with a dihedral angle of 38.3°. The magnetic properties of the complexes were elucidated. The temperature-dependent magnetic susceptibility of complex 5·Cu2Br6 shows the singlet–triplet transition with coupling constant J = −248 K, and that of 3·(CuBr4)0.5·CuBr3·THF shows the abrupt change at 270 K caused by the modulation of intermolecular interactions. The thermo variation of magnetic susceptibility for the other complexes follows the Curie–Weiss law, indicating the weak antiferromagnetic interaction at low temperature.
Keywords: antiferromagnetic interaction; arylthio-substituted tetrathiafulvalenes; charge-transfer; crystal structure; magnetic property

(untitled) - Wudl, F.; Smith, G. M.; Hufnagel, E. J. (J. Chem. Soc. D, 1970)

TTF Chemistry Fundamentals and Applications of Tetrathiafulvalene - Yamada, J.; Sugimoto, T. (Kodansha Springer, 2004)

(untitled) - Ferraris, J.; Cowan, D. O.; Walatka, V.; Perlstein, J. H. (J. Am. Chem. Soc., 1973)

(untitled) - Jérome, D.; Mazaud, A.; Ribault, M.; Bechgaard, K. (J. Phys., Lett., 1980)

Organic Superconductors (including Fullerenes) - Williams, J. M.; Ferraro, J. R.; Thorn, R. J.; Carlson, K. D.; Geiser, U.; Wang, H. H.; Kini, A. M.; Whangbo, M.-H. (Prentice Hall, 1992)

Organic Superconductors - Ishiguro, T.; Yamaji, K.; Saito, G. (Springer, 1998)

Molecular Conductors - Batail, P. (Chem. Rev., 2004)

Organic Conductors - Kagoshima, S.; Kanoda, K.; Mori, T. (J. Phys. Soc. Jpn., 2006)

The Physics of Organic Superconductors and Conductors - Lebed, A. (Springer, 2008)

(untitled) - Ardavan, A.; Brown, S.; Kagoshima, S.; Kanoda, K.; Kuroki, K.; Mori, H.; Ogata, M.; Uji, S.; Wosnitza, J. (J. Phys. Soc. Jpn., 2012)

(untitled) - Ota, A.; Yamochi, H.; Saito, G. (J. Mater. Chem., 2002)

(untitled) - Ota, A.; Yamochi, H.; Saito, G. (J. Low Temp. Phys., 2006)

(untitled) - Chollet, M.; Guerin, L.; Uchida, N.; Fukuya, S.; Shimoda, H.; Ishikawa, T.; Matsuda, K.; Hasegawa, T.; Ota, A.; Yamochi, H.; Saito, G.; Tazaki, R.; et al. (Science, 2005)

(untitled) - Onda, K.; Ogihara, S.; Yonemitsu, K.; Maeshima, N.; Ishikawa, T.; Okimoto, Y.; Shao, X.; Nakano, Y.; Yamochi, H.; Saito, G.; Koshihara, S.-y. (Phys. Rev. Lett., 2008)

(untitled) - Gao, M.; Lu, C.; Jean-Ruel, H.; Liu, L. C.; Marx, A.; Onda, K.; Koshihara, S.-y.; Nakano, Y.; Shao, X.; Hiramatsu, T.; Saito, G.; Yamochi, H.; et al. (Nature, 2013)

(untitled) - Shao, X.; Nakano, Y.; Yamochi, H.; Dubrovskiy, A. D.; Otsuka, A.; Murata, T.; Yoshida, Y.; Saito, G.; Koshihara, S.-y. (J. Mater. Chem., 2008)

(untitled) - Shao, X.; Nakano, Y.; Sakata, M.; Yamochi, H.; Yoshida, Y.; Maesato, M.; Uruichi, M.; Yakushi, K.; Murata, T.; Otsuka, A.; Saito, G.; Koshihara, S.-y.; et al. (Chem. Mater., 2008)

(untitled) - Shao, X.; Yoshida, Y.; Nakano, Y.; Yamochi, H.; Sakata, M.; Maesato, M.; Otsuka, A.; Saito, G.; Koshihara, S.-y. (Chem. Mater., 2009)

(untitled) - Murata, T.; Shao, X.; Nakano, Y.; Yamochi, H.; Uruichi, M.; Yakushi, K.; Saito, G.; Tanaka, K. (Chem. Mater., 2010)

(untitled) - Bryce, M. R. (Chem. Soc. Rev., 1991)

(untitled) - Adam, M.; Müllen, K. (Adv. Mater., 1994)

(untitled) - Jørgensen, T.; Hansen, T. K.; Becher, J. (Chem. Soc. Rev., 1994)

(untitled) - Bryce, M. R. (J. Mater. Chem., 1995)

(untitled) - Garín, J. (Adv. Heterocycl. Chem., 1995)

(untitled) - Otsubo, T.; Aso, Y.; Takimiya, K. (Adv. Mater., 1996)

(untitled) - Coronado, E.; Gómez-García, C. J. (Chem. Rev., 1998)

(untitled) - Bryce, M. R. (Adv. Mater., 1999)

(untitled) - Nielsen, M. B.; Lomholt, C.; Becher, J. (Chem. Soc. Rev., 2000)

(untitled) - Segura, J. L.; Martín, N. (Angew. Chem., Int. Ed., 2001)

(untitled) - Frère, P.; Skabara, P. J. (Chem. Soc. Rev., 2005)

(untitled) - Canavet, D.; Sallé, M.; Zhang, G.; Zhang, D.; Zhu, D. (Chem. Commun., 2009)

(untitled) - Ding, H.; Li, Y.; H, H.; Sun, Y.; Wang, J.; Wang, C.; Wang, C.; Zhang, G.; Wang, B.; Xu, W.; Zhang, D. (Chem. – Eur. J., 2014)

(untitled) - Skabara, P. J.; Serebryakov, I. M.; Roberts, D. M.; Perepichka, I. F.; Coles, S. J.; Hursthouse, M. B. (J. Org. Chem., 1999)

(untitled) - Skabara, P. J.; Roberts, D. M.; Serebryakov, I. M.; Pozo-Gonzalo, C. (Chem. Commun., 2000)

(untitled) - Berridge, R.; Serebryakov, I. M.; Skabara, P. J.; Ortí, E.; Viruela, R.; Pou-Amérigo, R.; Coles, S. J.; Hursthouse, M. B. (J. Mater. Chem., 2004)

(untitled) - Kanibolotsky, A. L.; Kanibolotskaya, L.; Gordeyev, S.; Skabara, P. J.; McCulloch, I.; Berridge, R.; Lohr, J. E.; Marchioni, F.; Wudl, F. (Org. Lett., 2007)

(untitled) - Sun, J.; Lu, X.; Shao, J.; Cui, Z.; Shao, Y.; Jiang, G.; Yu, W.; Shao, X. (RSC Adv., 2013)

(untitled) - Sun, J.; Lu, X.; Shao, J.; Li, X.; Zhang, S.; Wang, B.; Zhao, J.; Shao, Y.; Fang, R.; Wang, Z.; Yu, W.; Shao, X. (Chem. – Eur. J., 2013)

(untitled) - Lu, X.; Sun, J.; Liu, Y.; Shao, J.; Ma, L.; Zhang, S.; Zhao, J.; Shao, Y.; Zhang, H.-L.; Wang, Z.; Shao, X. (Chem. – Eur. J., 2014)

(untitled) - Sun, J.; Lu, X.; Ishikawa, M.; Nakano, Y.; Zhang, S.; Zhao, J.; Shao, Y.; Wang, Z.; Yamochi, H.; Shao, X. (J. Mater. Chem. C, 2014)

(untitled) - Lu, X.; Sun, J.; Zhang, S.; Ma, L.; Qi, H.; Liu, L.; Shao, Y. (Beilstein J. Org. Chem.)
The combination of Ar-S-TTFs with fullerenes resulted in various type of donor-acceptor type co-crystals.

(untitled) - Zhang, S.; Lu, X.; Sun, J.; Zhao, Y.; Shao, Y.; Shao, X. (CrystEngComm, 2015)
The supramolecular assembly of Ar-S-TTF with Keggin-type phosphomolybdic acid resulted in the honey-comb supramolecular frameworks.

(untitled) - Siedle, A. R.; Candela, G. A.; Finnegan, T. F.; Van duyne, R. P.; Cape, T.; Kokoszka, G. F.; Woyciejes, P. M.; Hashmall, J. A. (Inorg. Chem., 1981)

(untitled) - Inoue, M. B.; Inoue, M.; Fernando, Q.; Nebesny, K. W. (Inorg. Chem., 1986)

(untitled) - Day, P.; Kurmoo, M.; Mallah, T.; Marsden, I. R.; Friend, R. H.; Pratt, F. L.; Hayes, W.; Chasseau, D.; Gaultier, J. (J. Am. Chem. Soc., 1992)

(untitled) - Marsden, I. R.; Allan, M. L.; Friend, R. H.; Kurmoo, M.; Kanazawa, D.; Day, P.; Bravic, G.; Chasseau, D.; Ducasse, L.; Hayes, W. (Phys. Rev. B, 1994)

(untitled) - Iwamatsu, M.; Kominami, T.; Ueda, K.; Sugimoto, T.; Adachi, T.; Fujita, H.; Yoshino, H.; Mizuno, Y.; Murata, K.; Shiro, M. (Inorg. Chem., 2000)

(untitled) - Kanehama, R.; Umemiya, M.; Iwahori, F.; Miyasaka, H.; Sugiura, K.-i.; Yamashita, M.; Yokochi, Y.; Ito, H.; Kuroda, S.; Kishida, H.; Okamoto, H. (Inorg. Chem., 2003)

(untitled) - Matsumoto, T.; Kamada, Y.; Sugimoto, T.; Tada, T.; Noguchi, S.; Nakazumi, H.; Kawakami, T.; Yamaguchi, K.; Shiro, M. (Inorg. Chem., 2003)

(untitled) - Lu, W.; Zhu, Q.-Y.; Dai, J.; Zhang, Y.; Bian, G.-Q.; Liu, Y.; Zhang, D.-Q. (Cryst. Growth Des., 2007)

(untitled) - Ichikawa, S.; Kimura, S.; Takahashi, K.; Mori, H.; Yoshida, G.; Manabe, Y.; Matsuda, M.; Tajima, H.; Yamaura, J. (Inorg. Chem., 2008)

(untitled) - Wang, Y.; Cui, S.; Li, B.; Zhang, J.; Zhang, Y. (Cryst. Growth Des., 2009)

(untitled) - Ichikawa, S.; Takahashi, K.; Matsuda, M.; Tajima, H.; Mori, H. (J. Mater. Chem., 2010)

(untitled) - Guionneau, P.; Kepert, C. J.; Bravic, G.; Chasseau, D.; Truter, M. R.; Kurmoo, M.; Day, P. (Synth. Met., 1997)

(untitled) - Pavlyuka, O.; Lis, T.; Mys’kiv, M. G. (Z. Anorg. Allg. Chem., 2005)

(untitled) - Beck, J.; de Oliveira, A. B. (Z. Anorg. Allg. Chem., 2009)

(untitled) - Kubo, K.; Yamashita, M. (Crystals, 2012)

(untitled) - Bondi, A. (J. Phys. Chem., 1964)

Molecular Magnetism - Kahn, O. (Wiley-VCH, 1993)

(untitled) - Burla, M. C.; Caliandro, R.; Camalli, M.; Carrozzini, B.; Cascarano, G. L.; de Caro, L.; Giacovazzo, C.; Polidori, G.; Spagna, R. (J. Appl. Crystallogr., 2005)

SHELXL-97, A Program for Crystal Structure Refinement (University of Göttingen, 1997)

Landolt-Börnstein, New Series II - Gupta, R. R. (Diamagnetism Susceptibility, 1986)